Metaphorics of Browser Games in Historical, Media Studies and Metaphorological Perspectives - Babecki, Miłosz (Media - Culture - Social Communication, 2021)
In the years 2005/2006–2020, around 51 Polish browser metaphor games concerning threads from the recent history of Poland were released on the Internet. These applications were based on these main themes: the functioning of the parliamentary system; procedures of selecting persons for the highest offices; the performance of duties by politicians; attitudes towards some behaviours of the politicians; living conditions in Poland. These games did not present events occurring outside the media as if they were news broadcasts published in the press, radio and television. Polish developers decided to comment on this reality by reaching for metaphorical constructions. This study, therefore, pursues three main objectives. The first goal is to identify and describe the features that browser games must have to be able to convey metaphorical messages. The second objective is to show the evolutionary process of metaphorising Polish browser games, while the third goal is to explain how this process works.